Family Experience of Stroke Patients Regarding Prehospital Time: A Phenomenological Study - Risqi Wahyu Susanti; Abd. Gani Baeda; Ekawati Saputri (Jurnal Keperawatan Padjadjaran, 2022)
Background: Stroke is a neurological disease that requires immediate treatment, and family participation is very important when a stroke occurs at home. Purpose: This study aims to explore the pre-hospital time experiences of patients’ families with stroke in Kolaka Regency. Methods: The study is a qualitative research with a phenomenological design. A total of 8 participants from families of stroke patients were recruited using a purposive sampling approach. Source triangulation was used in this study from stroke patients. Data were collected through in-depth interviews using audio-recorded then transcribed verbatim and validated between researchers. The data were analyzed using colaizzi method with a selective and focused analysis approach to obtain themes. Results: There are two themes of this study, the first theme is responses of stroke and the second theme is medical treatment. Conclusion: It is important that family members have a good response and knowledge so that when one of their family members has a stroke, they can be taken to the hospital at the right time. Our suggestion is that it is necessary to increase family knowledge about stroke to minimize the delay in stroke rescue time.